MODEL POLA TANAM DAN STRUKTUR PEMANFAATAN RUANG KEMITRAAN PADA HUTAN PRODUKSI (Forum Ilmu Sosial, 2014)
The purpose of this study were: 1) assess the cropping pattern in the space of production forests, 2) assess the spatial structure of forest partnerships, and 3) The research was carried out in the forest of Muria Area - Pati Regency, in three areas of production forest administration and varied forest utilization patterns. The population is the pesanggem, spatial analysis was used to assess forest spatial structure of the partnership, the analysis of theMinimum Necessities of Life (KFM –Kebutuhan Hidup Minimum) and the find the optimized utilization of sustainable production forest area. cropping patterns, partnership space, pesanggem, structure, stands Proper Necessities of Life (KHL-Kebutuhan Hidup Layak) from farming activities in the forest. There were found that the patterns of space utilization of production forest do not meet the rules of partnership in Region Development (WPWilayah Pembangunan) I, yet it was appropriate in areas II and III. Pesanggem in regions I and III could cover the KHL, while the pesanggem in WP II were just to cover the KFM. Utilization patterns and structures to maintain a sustainable spatial quality have not made sovereign by the partners. It can be seen from the cropping pattern executed in each region in which the pattern of monoculture in WP I, 90% of total borgan area was occupied by cassava plantation, polyculture pattern in the WP II and compound pattern in the WP III. The suggestion is that the need to reform the partnership space on the production forest for economically and ecologically sustainable.